EXAMPLE OF INTEGRATED LESSON - THE STORY OF “Milky Way”: THE BREAD - Saparbaeva Ainura Abdilazimovna; Parpieva Aisuluu Abdizhalalovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2021)
The scientific article deals with the integration of subjects, their methods, the ability to reveal the relationship of subjects through the literary text, as a result of which the student learns interesting, comprehensive knowledge through joint practice. Properly selected learning technologies play an important role in the gradual advancement of knowledge. Variational programs or subjects cannot be considered in complete isolation. They will have the opportunity to join the educational space by integrating Kyrgyz literature and Kyrgyz language. It takes a long time for a student to achieve a goal. From this point of view, an encyclopedist is required to be a teacher. Integrated learning aims to increase the student’s level of knowledge and strives to achieve it effectively.